The Role of Bee Products in Cosmetic and Skincare Industry: Current Trends and Future Prospects - Gupta, Garima; Rawat, Divyanshi; Aggarwal, Rahul (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2024)
In recent years, honey-based products have gotten a lot of attention for the interesting and varied ways they can be used in cosmetics and skin care. Venom, royal jelly, honey, beeswax, and propolis are among the most well-known bee products. For the goal of healing and maintaining skin health, each part has its own special properties. This review article will examine the potential uses of bee products in the beauty and skincare industries. The purpose of this study is to synthesize previous research with current advancements in order to provide a thorough review of bee-derived compounds and their potential to transform the cosmetics industry. Each bee product is investigated for its distinct cosmetic uses, revealing information on how it moisturizes, rejuvenates, and protects the skin. It is the goal of this study to give a deep look into the latest market trends in honey-based skin care goods. As the need for options that are better for the environment and your skin grows, bee products have become a good choice. Knowing what chemicals are in them and how they can help with cosmetics gives both customers and professionals in the field useful information to help them make smart decisions. This review also shows the current trends in the skin care market, which helps us understand the future of bee products in the beauty business. Consumers are looking for eco-friendly and effective ways to take care of their skin, so honey-based cosmetics are likely to become more popular.